Effect of Teaching Methods on Achievement Level of Students: Exploring the Impact of Teaching Methods on Student Achievement (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In light of heightened teacher responsibility, student accomplishment became a hot subject ineducation. Any teacher's ultimate objective is to raise pupils' aptitude levels and get them ready formaturity. Being an effective teacher requires understanding what constitutes student accomplishment andwhat variables affect learning. The quantity of academic material a students acquire in a given period oftime is measured as student accomplishment. There are learning objectives or instructional standards foreach grade level that teachers must follow. There are several factors that may affect how well students do,but the most important ones are learning difficulties and instructional strategies. The best way tocharacterise a teaching approach is the kind of principle and instructional techniques employed. Variousteaching techniques exist, based on the knowledge or skill the instructor is attempting to impart.